Lasers in advanced clinical dental practice: A review - Niranjala Mohad (Bioinformation, 2026)
Conventional soft tissue surgical techniques in dentistry are often limited by inadequate precision, increased intraoperative bleeding and post-operative discomfort, underscoring the need for more effective and minimally invasive approaches such as diode laser technology in clinical practice. Therefore, it is of interest to evaluate the expanding role of diode lasers, focusing on their clinical applications, advantages, limitations and future scope. Diode lasers are widely employed in soft tissue interventions such as frenectomy, gingivectomy, operculectomy, lesion excision and biopsies, offering benefits like enhanced haemostasis, reduced bleeding, minimal post-operative discomfort and accelerated healing. Thus, data shows that diode lasers represent a valuable adjunct in clinical practice, though further standardised research is necessary to optimise their application.